Membrane “potential-omics”: toward voltage imaging at the cell population level in roots of living plants - Matzke, Marjori; Matzke, Antonius J. (Frontiers in Plant Science, 2013)
Genetically-encoded voltage-sensitive fluorescent proteins are being used in neurobiology as noninvasive tools to study synchronous electrical activities in specific groups of nerve cells. Here we discuss our efforts to adapt this ‘light-based electrophysiology’ for use in plant systems. We describe the production of transgenic plants engineered to express different versions of voltage-sensitive fluorescent proteins that are targeted to the plasma membrane and internal membranes of root cells. The aim is to optically record concurrent changes in plasma membrane potential in populations of cells and at multiple membrane systems within single cells in response to various stimuli in living plants. Such coordinated electrical changes may globally orchestrate cell behavior to elicit successful reactions of the root as a whole to varying and unpredictable environments. Findings from membrane ‘potential-omics’ can eventually be fused with data sets from other ‘omics’ approaches to forge the integrated and comprehensive understanding that underpins the concept of systems biology.